The color Doppler twinkling artifact of implants after endoscopic treatment of vesicoureteral reflux in children: A common finding with high potential for misdiagnosis. Issue 5 (October 2021) - Steinborn, Marc; Kehrer, Lara; Kabs, Carmen; Hosie, Stuart; Huf, Veronika
Summary: Background: Endoscopic treatment of vesicoureteral reflux (VUR) is a common therapeutic procedure in children. Over the last years several studies reported on calcified deflux implants that were misinterpreted as ureteral stones leading to unnecessary diagnostic and therapeutic procedures. Objective: Based on an own case, where a calcified implant with a strong twinkling artifact was misdiagnosed as a ureteral stone, the purpose of our study was to evaluate the sonographic imaging appearance of implants after endoscopic VUR repair with special emphasis on the color twinkling artifact. Material and methods: In 40 children (mean age 9.5 years) with 62 treated ureteral units follow-up sonography was performed after a mean time interval of 48.8 months after surgery. The injected deposit was evaluated with B-mode sonography and color Doppler sonography and deposit volume, posterior acoustic shadowing and the appearance and extension of the twinkling artifact were evaluated. Results: 47 of 62 injected units (75.8%) could be identified on follow-up sonography. In 13 of 47 units (27.7%) posterior acoustic shadowing was noted. On color Doppler sonography a twinkling artifact appeared in 26 of the 47 visible cases (55.3%). There was a statistically significant correlation between a positive twinkling sign and the deposit age. Conclusion: In conclusion our study shows that the twinkling artifact is a common finding in follow-up sonography of children after endoscopic treatment of VUR. As the twinkling artifact is a sensitive imaging sign for the detection of ureteral calculi the risk of misinterpretation and mistreatment is given. Ultrasound image of a 12y old boy with left sided abdominal pain. History of left sided VUR IV° and endoscopic treatment 11 years ago. Color doppler sonogram shows strong twinkling artifact behind the bladder on the left side erroneously interpreted as a ureteral calculus. Image 1